Urban energy systems for low-carbon cities - Eicker, Ursula (Academic Press, an imprint of Elsevier, 2019)
With an increase of global energy demand arising in urban settlements, the key challenges for the urban energy transition include analysis of energy efficiency options and the potential of renewable energy systems within the existing building stock, making cities a key actor in the transition success. In Urban Energy Systems for Low Carbon Cities, indicators to evaluate urban energy performance are introduced and the status quo of monitoring and efficiency valuation schemes are discussed. The book discusses advances on the state-of-the-art of research in a number of key areas: Energy demand and consumption mapping and monitoring Optimization of design and operation of urban supply and distribution systems Integration of renewable energy and urban energy network models Demand side management strategies to better match renewable supply and demand and increase flexibilities With innovative modelling methods this book gives a real bottom-up modelling approach used for the simulation of energy consumption, energy conversion systems and distribution networks using engineering methods.